Studi Pembuatan Puding Kombinasi Belimbing Wuluh dan Jambu Biji Merah Sebagai Alternatif Makanan Selingan Sumber Antioksidan - Siti Nuridni Fajriyah; Huda Oktafa (Politeknik Negeri Jember, 2020)
The results of Riskesdas 2018 show an increase in the prevalence of degenerative diseases in Indonesia such as cancer, heart disease, and hypertension. Degenerative diseases caused by an imbalance between the amount of free radicals and antioxidants in the body. This study aims to produce a pudding with combination of star fruit and red guava fruit as an alternative snack of antioxidant sources. The experimental design was a Completely Randomized Design with six treatment which are the proportion guava fruit and star fruit are 80% : 20%, 70% : 30%, 60% : 40%, 50% : 50%, 40% : 60%, 30% : 70% and repeated four times. Analysis on the product are chemical (antioxidant) and organoleptic analysis. The results showed that the pudding has a significantly different (P<0,05) to antioxidant activity, hedonic quality on color, taste, aroma, and hedonic test of color, taste, aroma. The pudding with combination of star fruit andÂ red guava fruit in various formulations had no effect on the organoleptic test (hedonic and hedonic quality on texture). The best treatment is P1 with a 80% formulation of red guava fruit and 20% of star fruit which contained 38,67% antioxidant activity. The nutritional facts of 100 grams pudding has 50,81 kcal of energy, 0,37 grams of protein, 1,53 grams of fat, and 47,8 grams of carbohydrates